Influence Of Competence, Work Discipline, And Motivation On The Performance Of Employees In The Regional Revenue Service In Palembang City - Yustini, Tien Yus; Kurniawan, Endi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: this study aims to examine the influence of competence, work discipline, and motivation on the performance of employees at the Palembang City Regency Service. Methodology: The research employed a quantitative approach using a survey method. Data were collected from 100 employees through structured questionnaires and analyzed using multiple regression analysis to determine the relationship between independent variables (competence, work discipline, motivation) and the dependent variable (employee performance). ResultsThe results indicate that competence, work discipline, and motivation significantly affect employee performance. Among these, motivation was found to have the strongest influence, followed by competence and work discipline. Findings: The study reveals that improving employee motivation, alongside enhancing competence and enforcing work discipline, can lead to better performance outcomes in the Palembang City Regency Service. Novelty: This research provides new empirical evidence on the combined effect of competence, work discipline, and motivation specifically within the context of local government services in Palembang City, an area with limited prior research on this topic. Originality: The originality of this paper lies in its focus on public sector employees in the Palembang City Regency Service, offering practical insights for local government management to optimize employee performance. Conclusion: Competence, work discipline, and motivation are critical determinants of employee performance. Strategies aimed at developing these factors should be prioritized to improve service delivery in the Palembang City Regency Service. Type of Paper: research article.